1994
DOI: 10.1063/1.466252
|View full text |Cite
|
Sign up to set email alerts
|

Surface segregation in polymer blends due to stiffness disparity

Abstract: The entropy-driven surface segregation of polymer blends is investigated via computer simulations and integral equation theory. The model system is composed of a binary blend at a hard wall where one of the components of the blend is stiffer than the other. It is found that, at meltlike densities relevant to experiments, both simulations and microscopic theory predict the segments of the stiffer chains segregate to the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
91
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 17 publications
13
91
3
Order By: Relevance
“…In particular, we find that smaller species segregate to the neutral surface, as expected. In the blend, we find the enrichment of the neutral surface by chains, which has been suggested earlier for small structural differences [30,31,36]. However, our results are inconsistent with the known results [31b,36] on the behaviour of endgroups and surface enrichment in the above blend.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In particular, we find that smaller species segregate to the neutral surface, as expected. In the blend, we find the enrichment of the neutral surface by chains, which has been suggested earlier for small structural differences [30,31,36]. However, our results are inconsistent with the known results [31b,36] on the behaviour of endgroups and surface enrichment in the above blend.…”
Section: Discussioncontrasting
confidence: 57%
“…Hence, such a theory allows us to predict many of these microscopic parameters like the chi parameter from experimental measurements, provided the theory is based on a realistic model of the system. Current interest has been to understand whether architecture plays an important role in determining nonuniversal properties like the effective chi parameter and behaviour near surfaces, or universal properties like the exponents [17,20,22,23,26,[28][29][30][31][32][33][34][35][36][37][38]42,43]. Statistical mechanics also enables us to separate out the entropic contribution from the energetic contribution to understand the effect of architectural differences.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that for polymer blends composed of polymers with different degree of polymerization but of chemically identical monomers, shorter polymers are in excess at the wall. It was also demonstrated in simulations [4,11] and supported by calculations using the integral equation theory [18] that stiffer polymers are present in excess in the vicinity of the wall. However the self-consistent field theory developed in Ref.…”
Section: Introductionmentioning
confidence: 92%
“…Recently there has been a big deal of attention on the surface segregation due to conformational asymmetry of the molecules of the polymer blend and due to differences in topology [4,8,9,10,11,12,13,14,15,16,17]. It was established that the composition of polymer blends in the vicinity of surfaces can be different from the bulk composition even for neutral surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation